(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The effectiveness Protected areas (PAs) significantly depends on their management and planning strategies. This study examined the key challenges for environmental management in the Korgalzhyn State Nature Reserve (KSNR) in Kazakhstan. An understanding of these difficulties is essential in developing the key evaluation indicators for implementation of effective management to KSNR. Semi-structured interviews were conducted with stakeholders (representatives of the local authority, non-governmental organisations, international organisations, KSNR staff) as well as with local people to understand the perception and attitude of interviewees towards KSNR. The collected data then analysed with coding. The results indicate that the main challenges to effective management in the KSNR are limited stakeholders’ participation in decision-making processes and inadequate financial benefits. In addition, there is still a negative attitude towards the KSNR as a result of restricted access to the PA. Limited public engagement is another obstacle to implementing sustainability principles in the KSNR management system. It is important to effectively engage more residents in environmental education that could change people’s perception towards the reserve and behaviour. These challenges provide directions/local points for identifying and developing possible key indicators for evaluation of PAs’ management system. Key words: environmental management, protected area, Korgalzhyn State Nature Reserve, public perception, stakeholders.